Improving the flavour of cheese - Weimer, Bart C. (Woodhead Publishing in food science, technology, and nutrition., 2007)
Flavour is key to the acceptance of cheese products among consumers and is therefore a critical issue for professionals in the dairy industry. However, the manufacture of cheeses that are consistently safe and flavourful often eludes scientists. Developments such as high throughput genome sequencing and metabolite analysis are having a significant impact on research, leading to the development of new tools to control and improve the flavour of cheese. With contributions from an international array of acclaimed authors, Improving the flavour of cheese, provides crucial reviews of recent research in the field. The book begins with a summary of cheese ripening and the compounds associated with cheese flavour. Part one discusses the metabolism of specific substrates to flavour compounds by microbes associated with milk and cheese. Part two reviews the influence of ingredients, processing and certain chemical and physical factors on cheese flavour. Part three addresses the measurement of cheese flavour. The book concludes with a selection of case studies on specific product types such as hard Italian, brined cheese, as well as low fat and soft-ripened cheeses. Improving the flavour of cheese provides a unique review of emerging techniques and ideas to control the flavour of cheese. This original book will be a standard reference for those concerned with the development and manufacture of cheese. Discusses the wealth of research in the area of flavour developmentReviews the influence of ingredients, processing and certain chemical and physical factors on cheese flavourConcludes with a selection of case studies on specific product types.